Projection Methods for a System of Nonlinear Mixed Variational Inequalities in Banach Spaces - Zhong-Bao Wang; Guo-Ji Tang; Hong-Ling Zhang (Journal of Function Spaces)
The existence and uniqueness of solution for a system of nonlinear mixed variational inequality in Banach spaces is given firstly. A Mann iterative sequences with errors for this system of nonlinear mixed variational inequalities in Banach spaces is studied, by using the generalized f-projection operator πKf. Our results extend the main results in (Verma (2005); Verma (2001)) from Hilbert spaces to Banach spaces.